Prevalence, phenotypic, and genotypic assessment of antibiotic resistance, virulence markers and molecular typing of Staphylococcus epidermidis strains isolated from bovine subclinical mastitic milk. - Talebi, Fatemeh; Momtaz, Hassan; Bamzadeh, Zahra (2021)
Staphylococcus epidermidis is one of the causative agents of bovine mastitis with an emergence of antibiotic resistance and virulence characters. One hundred and three mastitic milk samples were collected and confirmed through the use of the California mastitis test. Samples were cultured and S. epidermidis isolates were identified by Loop mediated isothermal amplification (LAMP) method. Molecular typing of S. epidermidis isolates was performed using the Multiple-locus variable-number tandem repeat analysis (MLVA). Eighteen out of 103 (17.47%) samples were positive for S. epidermidis. S. epidermidis isolates exhibited the uppermost prevalence of resistance toward penicillin (100%), tetracycline (83.33%), erythromycin (83.33%), and cefazolin (77.77%). ClfA (55.55%), agrI (50%), etA (33.33%), and agrIII (27.77%) were the most routinely identified virulence factors. TetM (88.88%), aacA-D (83.33%), tetK (77.77%), ermA (72.22%), msrA (55.55%), and ermC (55.55%) were the most routinely identified antibiotic resistance genes. A total of five separate loci (se1 to se5) were originated amongst 18 S. epidermidis isolates. Seventeen isolates were classified into one similar molecular cluster. The existing survey is an initial report of genetically characteristic of virulence factors and antibiotic resistance markers and MLVA-based typing of S. epidermidis bacteria isolated from bovine clinical mastitis milk. Similar genetical profile of S. epidermidis bacteria signifies the same sources of infections. The anthropogenic nature of S. epidermidis may display that infected
milkers were the main source of udder infection.
Keywords: Resistance to antibiotics; Virulence; Bovine mastitis